Pengaruh kombinasi terapi musik dan story telling terhadap kecemasan pemasangan infus pada anak pra sekolah - Arum Uswatun Khasanah; Indriyati Indriyati; Atik Aryani (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Preschool-aged children are highly active, which can lead to fatigue, making them more susceptible to illness. Based on the Orchid Room medical record data from Dr. Soehadi Prijonegoro Hospital, Sragen, the number of preschool patients in the Orchid Room in 2024 was 154. Anxiety among preschool children at Dr. Soehadi Prijonegoro Hospital, Sragen, in 2024 was 70%. Anxiety can be addressed through pharmacological and non-pharmacological approaches. Non-pharmacological therapies include music therapy and storytelling. Purpose: To determine the effect of a combination of music therapy and storytelling on anxiety related to IV insertion in preschool children. Method: This study used a quantitative pre-experimental approach, with a one-group pre-test-post-test design. Anxiety in preschool children was measured using the Preschool Anxiety Scale questionnaire. A purposive sampling method was used for 20 respondents. Data were analyzed using a paired t-test. Results: Univariate analysis revealed that the anxiety level of IV insertion in preschool children before the combination of music therapy and storytelling was moderate (90%) and decreased after the combination of music therapy and storytelling to mild anxiety (90%). The paired t-test yielded a p-value of 0.000 (<0.05). Conclusion: The combination of music therapy and storytelling significantly impacts anxiety related to IV insertion in preschool children